FRI0239 ANTI-NXP2 ANTIBODIES: CLINICAL AND SEROLOGICAL ASSOCIATIONS IN A MULTICENTRIC ITALIAN STUDY. (2nd June 2020) - Fredi, M.; Cavazzana, I.; Ceribelli, A.; Lazzaroni, M. G.; Barsotti, S.; Benucci, M.; Cavagna, L.; De Stefano, L.; Doria, A.; Emmi, G.; Fornaro, M.; Furini, F.; et al.
Abstract : Background: anti-NXP2 antibodies is considered a serological marker of dermatomyositis (DM), with calcinosis, severe myositis and, in some series, cancer. Historically, these associations have been detected with immunoprecipitation (IP), but in the last few years commercial lineblot (LB) assay have been released. Objectives: to analyze the clinical features associated to anti-NXP2 antibodies, including the onset of concomitant cancers, both with LB and homemade IP Methods: clinical and serological data from medical charts of 213 patients with a diagnosis of inflammatory miosidites without anti-NXP2 (NXP2-), followed-up by two third-level Centers, and 61 anti-NXP2+ patients from 10 Rheumatological centers were analyzed. Anti-myositis specific (MSA) and anti-myositis associated antibodies (MAA) were detected in single centers by LB (Euroimmun Autoimmune Inflammatory Myopathies 16 antigens). Anti-NXP2 was confirmed by protein and RNA IP, as previously described (1) Results: clinical diagnosis of anti-NXP2+ positive with LB were 42 DM, 11 PM, inclusion body myositis (IBM) 4, necrotizing myositis and overlap (OM) 1 each. Anti-NXP2+ showed a lower age at onset (p<0.0001) more frequent diagnosis of DM (68.8%vs30%, OR5.2) and IBM (6.5%vs0.49%, OR14.8), typical skin manifestations, myositis (93%vs79% OR3.3), concomitant presence of another MSA (12.7%vs2%, OR6.41) and lower rate of features associated with OM or anti-synthetase syndrome. Serum from 49 NXP2+ was available and IP analysis was made with the confirmation of NXP2 in 31 sera (63.2%) with the following diagnosis: DM 27 cases, PM 3, IBM 1. Whilst the majority of the associations were confirmed comparing NXP2LB+/IP+ with the IIM NXP2-, some peculiar associations were found significant only for the double positive patients: dysphagia (53%vs 30%, OR 2.56) and calcinosis (22%vs6.5% OR4) whereas IBM diagnosis and the presence of concomitant MSA antibodies were lost. Survival time from cancer onset is shown in figure. IP did not confirmed anti-NXP2 antibodies in 18 sera: in 4 cases at least one MSA/MAA was identified by IP; these 18 patients did not show differences when compared with 213 anti-NXP2-. Conclusion: Protein IP confirmed anti-NXP2 antibodies in 63% of LB+ sera. Double positive cases showed more typical DM features and rarely occurred in IIM not DM. Anti-NXP2 positivity by LB should be confirmed by other methods in order to correctly diagnose and characterize IIM patients. References: [1]Arthritis Res Ther 2012, 30;14:R97 Acknowledgments: Forum Italiano per la Ricerca Malattie Autoimmuni (FIRMA) Disclosure of Interests: Micaela Fredi: None declared, Ilaria Cavazzana: None declared, Angela Ceribelli: None declared, Maria Grazia Lazzaroni: None declared, Simone Barsotti: None declared, Maurizio Benucci: None declared, Lorenzo Cavagna: None declared, Ludovico De Stefano: None declared, Andrea Doria Consultant of: GSK, Pfizer, Abbvie, Novartis, Ely Lilly, Speakers bureau: UCB pharma, GSK, Pfizer, Janssen, Abbvie, Novartis, Ely Lilly, BMS, Giacomo Emmi: None declared, Marco Fornaro: None declared, Federica Furini: None declared, Roberto Gerli: None declared, Maria Grazia Giudizi: None declared, Marcello Govoni: None declared, Anna Ghirardello: None declared, Luca Iaccarino Speakers bureau: GSK, Pfizer, Janssen, Novartis, Florenzo Iannone Consultant of: Speaker and consulting fees from AbbVie, Eli Lilly, Novartis, Pfizer, Roche, Sanofi, UCB, MSD, Speakers bureau: Speaker and consulting fees from AbbVie, Eli Lilly, Novartis, Pfizer, Roche, Sanofi, UCB, MSD, Maria Infantino: None declared, Alessandro Mathieu: None declared, Emiliano Marasco: None declared, Paola Migliorini: None declared, Boaz Palterer: None declared, paola parronchi: None declared, Matteo Piga: None declared, Federico Pratesi: None declared, Antonella Radice: None declared, Carlo Selmi: None declared, Valeria Riccieri: None declared, Marilin Tampoia: None declared, Giovanni Zanframundo: None declared, Angela Tincani: None declared, Franco Franceschini: None declared